Development Of STEM Experiment Video For Science Learning : Water Wheel - Akbar, Anne Zelia; Muttaqiin, Arief (Department of Science Education, 2024)
This study aims to develop STEM-critical thinking-oriented science experiment videos: a water wheel on the material energy in living systems (VKA) for students, as well as investigate the validity and practicality of the developed video experiments. The type of research used is the development of the Plomp model which consists of three stages, namely preliminary research, prototyping stage, and assessment phase. However, due to time constraints, this research was limited to the prototyping stage. This research was conducted at SMP Negeri 1 Sintuk Toboh Gadang. In this study, researchers used instruments in the form of validity and practicality questionnaires. The results of the validity test and practicality test were analyzed using the Moment Kappa formula. The validity test was carried out by involving three science education lecturers at FMIPA UNP and the practicality test was carried out on 9 class VII4 students at SMP Negeri 1 Sintuk Toboh Gadang. The results of this study resulted in a VKA which obtained a validity test of 0.78 with high validity. While the practicality test on the one-to-one test was 0.86 with a very high practicality category, the small group test on students was 0.87 with a very high practicality category. It can be concluded that VKA has a high level of validity and a very high level of practicality.